The Authenticity of the Word in the Expression “Yahweh Touching Jeremiah’s Mouth” (Jer 1:4-10) - Viktorahadi, R. F. Bhanu (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
The prophetical offices are always started with prophetic call narrative. There are several unique elements in this prophetic call narrative, which can be found in prophetic call moments of the prophets, namely the role of God’s Words, the appearance of God (theophany) in its variety, and the delegation mission task. What is interesting to analyze is the variety of God’s appearances (theophany), since the varieties depend on the context of each prophet and the delegation mission tasks given to them. This article discusses the prophetic call narrative of Jeremiah. At first sight, the calling and delegation moments of Jeremiah resembles Isaiah and Ezekiel’s, especially in God’s hands and the prophet’s mouth activity. Nevertheless, in Jeremiah’s prophetic call narrative, God’s activities have a special meaning related to his context. In Jeremiah’s case, the act of God touching his mouth and putting His words into it is the emphasis of the authenticity of God’s Words that comes out of Jeremiah’s mouth. The authenticity is needed by Jeremiah because he has to face false prophets.